An Innovative Indicator System and Group Decision Framework for Assessing Sustainable Development Enterprises - Deng, Xiang (Springer Nature, 2020)
Empirical research suggests that companies pursuing sustainable development have higher credit ratings and lower equity costs. However, a review of the literature shows that no consensus has been reached regarding sustainable development indicators or appropriate decision-making methods for investment in sustainable development enterprises (SDEs). To address this gap, we build a set of sustainable development indicators to guide investors in assessing SDEs, allowing for more informed investment decisions regarding these potential opportunities. Next, to account for the subjectivity of the indicators and the relative weight of investors in group decision-making, we combine a q-rung orthopair fuzzy set with the multiplicative multi-objective optimization by ratio analysis method and introduce an optimization-based consensus model. Finally, we verify the validity of the proposed framework using a practical example. This framework has practical signiﬁcance for real-world SDE investment and contributes to the literature by introducing a new approach to multi-attribute group decision-making problems.